Gender-Age Association in Chronic Obstructive Pulmonary Disease (COPD): A Retrospective Cohort Study - Nur ‘Ainatul ‘Aisyah Samsudin; Fairuz Mohd Nasir; Azlinawati Ali; Nurul Fadhlina Ismail (Asian Journal of Medicine & Health Sciences, 2023)
Chronic obstructive pulmonary disease (COPD) is a significant global public health concern, also prevalent in Malaysia, contributing substantially to morbidity and mortality. The objective is to investigate COPD's prevalence while exploring its correlation with gender and age groups. A retrospective cohort investigation encompassed patients undergoing PA chest x-rays for suspected COPD at Damai Service Hospital (DSH) HQ in Kuala Lumpur from January 1, 2020, to December 31, 2021. Patient data, drawn from the 2020-2021 patient records, included 120 individuals with suspected COPD. These subjects were categorized by gender (male and female) and age groups (0-20, 21-40, 41-60, 61-80, and 81-100 years). Retrieval of confirmed COPD cases relied on the Radiology Information System (RIS), yielding 63 patients. Males constituted 66.7% of the 63 confirmed COPD cases, while females comprised 33.3%. COPD prevalence was highest in the 4160 age group (52.3%), followed by 30.1% in the 61-80 age group, 12.6% in the 21-40 age group, and 4.8% in the 81-100 age group; no cases appeared in the 1-20 age group. Notably, males aged 41-60 exhibited elevated COPD susceptibility. The study demonstrates a gender-age association in COPD patients, emphasizing males' heightened risk within the 41-60 age. The prevalence of COPD diagnosed from chest X-rays between 2020 and 2021 is 51.7%, predominantly among males (71.4%) and the 41-60 age group (52.3%). Notably, gender and age showed significant associations with COPD (p < 0.004, p < 0.047), highlighting crucial demographic factors.